Influence of Seaweed Liquid Fertilizer on Growth and Biochemical Characteristics of Arachis hypogea L. under field trial - Sridhar, S; Rengasamy, R (Journal of Ecobiotechnology, 2012)
In the present study, an attempt has been made to investigate the effect of Seaweed Liquid Fertilizer (SLF) of the brown seaweed Sargassum wightii Grev. on the growth, biochemical and pigment characteristics of Arachis hypogea. The 1.0% concentration of water extract showed better results of growth parameters, biochemical and pigments constitutions. Combined effect of 1.0% SLF plus different proportions of recommended rate of chemical fertilizers were also made on A. hypogea. Among the different concentrations of SLF investigated, the plants that received with 1.0% SLF showed maximum fresh weight, dry weight, root and shoot length, number of branches, leaf area and content of total chlorophyll, chlorophyll a and b, protein, carbohydrate and lipid. Similarly the plants that applied with 1.0% SLF plus 25% recommended rate of chemical fertilizers showed enhanced characteristics. Arachis hypogea treated with 1.0% SLF of S. wightii plus 25% recommended rate of chemical fertilizers showed an increased the above parameters.